Characteristics of Non-Muscle Invasive Bladder Cancer (NMIBC) in Patients Treated in an Indonesian Tertiary Hospital from 2008 to 2019 - Ferry Safriadi; I Nyoman Palgunadi (Faculty of Medicine, Universitas Padjadjaran, 2022)
Bladder cancer is the 10th most common cancer in both males and females with a ratio of 3:1. About 75% of bladder cancers are non-muscle invasive bladder cancers (NMIBC). The aim of this study was to identify the characteristics of Non-Muscle Invasive Bladder Cancer (NMIBC) patients treated in Dr. Hasan Sadikin General Hospital as one of the tertiary hospitals in Indonesia. This was a retrospective descriptive study that involved reviewing the medical records of patients diagnosed with NMIBC between January 2008 and December 2019. Characteristics reviewed were age, gender, body mass index (BMI), smoking history, urinary tract infection and stone history, intravesical chemotherapy and its side effects, and urinary cytology results. All data were tabulated and charted. Fifty-one out of 773 bladder cancer patients were diagnosed with NMIBC (6.59%). The mean age was 62.94 years old, with the majority of patients were in the 60-69 age group (31.37%). Males constituted the majority of the patients (n=44, 86.27%), with most patients had ideal BMI (66.66%), smoking history (72.54%), urinary tract infection history (56,86%), and urolithiasis history (5.88%). Thirty patients were given intravesical chemotherapy (58.82%), three patients experienced hematuria (10%), and four patients had painful urination (13.33%). Urinary cytology showed atypical cells (92.16%) in the majority of patients. The incidence of NMIBC in bladder cancer patients in our study was 6.59%, which differs from the incidence in developed countries of 75%, as shown in previous literature.